A T-shaped Ni[κ2-(CF2)4–] NHC complex: unusual Csp3–F and M–CF bond functionalization reactions. Issue 11 (6th August 2015) - Andrella, Nicholas O.; Sicard, Alexandre J.; Gorelsky, Serge I.; Korobkov, Ilia; Baker, R. Tom
Abstract : The reactivity of this T-shaped perfluoronickelacyclopentane–NHC complex with Lewis- and Brønsted acids is enhanced vs. 4-coordinate variants by its low coordination number. Abstract : A T-shaped octafluoronickelacyclopentane–NHC complex is prepared and characterized. While the solid-state structure includes a weak isopropyl-CH3 agostic interaction, the reactivity of this complex with Lewis- and Brønsted acids is clearly enhanced by its low coordination number. Reaction with Me3 SiOTf, for example, yielded a rare metal–heptafluorocyclobutyl complex whereas carboxylic acids gave substitution at the α-carbon and/or Ni–C F bond protonolysis to afford thermally robust 4 H -octafluorobutyl Ni complexes.